Effects of X-ray accelerating voltage on electrical properties and reliability for ferroelectric random-access memory (FeRAM). (1st March 2022) - Lin, Hsin-Ni; Chang, Ting-Chang; Chen, Wen-Chung; Tan, Yung-Fang; Chang, Kai-Chun; Lin, Shih-Kai; Yeh, Yu-Hsuan; Wu, Chung-Wei; Zhang, Yong-Ci; Yeh, Chien-Hung; Lee, Ya-Huan; Huang, Jen-Wei
Abstract: This work investigates the effect of X-ray accelerating voltage ( V acc ) on the structural repair of HfZrOx ferroelectric random-access memory. We found that X-rays are able to break the molecular bonds due to missing electrons, thereby repairing the material structure. To further understand the influence of X-ray V acc on structural repair, we conducted different V acc conditions, with results showing that there is only a small improvement under high V acc . However, the improvement is much clearer under low V acc . To illuminate these results, we propose a physical model which is based on different X-ray energies that will have different energy penetration capacities.